Simone Biles - Mugford, Simon; Green, Dan (London : Welbeck Children's Books, 2024)
This book is a fan guide that follows Simone Biles' journey to become a famous gymnast. Discover what drives her, the pressures she has faced, and the struggles that she has overcome, as well as all the details of her triumphs and her routines.
3-6
Keywords: Biles, Simone, -- 1997- -- Juvenile literature; Gymnasts -- United States -- Biography -- Juvenile literature; Biles, Simone, -- 1997-; Gymnasts; African Americans -- Biography; Women -- Biography; Biographies